Brewing Loyalty On The Move: The Role Of Food Quality, Price, And Variety On Customer Buying Decision Toward Kopi Keliling In Surabaya - Oliandes Sondakh; Edward Melvin Gandakusuma; Renna Magdalena (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2025)
This study investigates the impact of food quality, price, and menu variety on customer buying decisions among consumers of kopi keliling in Surabaya, a growing segment within Indonesia’s informal food and beverage industry. The research aims to provide insights into consumer behavior and offer practical recommendations for street-level entrepreneurs operating in dynamic urban markets. Using multiple linear regression analysis, the results reveal that food quality and menu variety significantly and positively influence buying decisions, while price despite being positively correlated, does not have a statistically significant effect. Among the three variables, food quality emerged as the strongest predictor, highlighting customers’ prioritization of taste, freshness, hygiene, and presentation. This supports previous findings, suggesting that consistency and quality are crucial to building trust and encouraging repeat purchases, especially in informal or mobile business settings. Menu variety also plays a vital role in shaping customer decisions. A diverse selection of coffee and beverage options helps vendors cater to different preferences and enhances the perceived value of the overall offering. In contrast, the insignificance of price indicates that consumers are more influenced by value perception than affordability alone challenging common assumptions about price sensitivity in informal market segments. The model’s Adjusted R² of 0.393 indicates that 39.3% of the variation in buying decisions can be explained by the three independent variables, while other potential factors such as service quality, vendor personality, and branding may also play a role.